Recruited Alveolar Macrophages, in Response to Airway Epithelial–Derived Monocyte Chemoattractant Protein 1/CCL2, Regulate Airway Inflammation and Remodeling in Allergic Asthma - Lee, Yong Gyu; Jeong, Jong Jin; Nyenhuis, Sharmilee; Berdyshev, Evgeny; Chung, Sangwoon; Ranjan, Ravi; Karpurapu, Manjula; Deng, Jing; Qian, Feng; Kelly, Elizabeth A. B.; Jarjour, Nizar N.; Ackerman, Steven J.; et al. (American journal of respiratory cell and molecular biology, 2015)
Although alveolar macrophages (AMs) from patients with asthma are known to be functionally different from those of healthy individuals, the mechanism by which this transformation occurs has not been fully elucidated in asthma. The goal of this study was to define the mechanisms that control AM phenotypic and functional transformation in response to acute allergic airway inflammation. The phenotype and functional characteristics of AMs obtained from human subjects with asthma after subsegmental bronchoprovocation with allergen was studied. Using macrophage-depleted mice, the role and trafficking of AM populations was determined using an acute allergic lung inflammation model. We observed that depletion of AMs in a mouse allergic asthma model attenuates Th2-type allergic lung inflammation and its consequent airway remodeling. In both human and mouse, endobronchial challenge with allergen induced a marked increase in monocyte chemotactic proteins (MCPs) in bronchoalveolar fluid, concomitant with the rapid appearance of a monocyte-derived population of AMs. Furthermore, airway allergen challenge of allergic subjects with mild asthma skewed the pattern of AM gene expression toward high levels of the receptor for MCP1 (CCR2/MCP1R) and expression of M2 phenotypic proteins, whereas most proinflammatory genes were highly suppressed. CCL2/MCP-1 gene expression was prominent in bronchial epithelial cells in a mouse allergic asthma model, and in vitro studies indicate that bronchial epithelial cells produced abundant MCP-1 in response to house dust mite allergen. Thus, our study indicates that bronchial allergen challenge induces the recruitment of blood monocytes along a chemotactic gradient generated by allergen-exposed bronchial epithelial cells.